2019
DOI: 10.1002/msc.1401
|View full text |Cite
|
Sign up to set email alerts
|

The skills, knowledge and attributes needed as a first‐contact physiotherapist in musculoskeletal healthcare

Abstract: Objectives The provision of musculoskeletal assessment and pathway management by physiotherapists in primary care is an expanding innovation within the UK National Health Service. This new model of care is challenging physiotherapists to work in new ways, and so an understanding of these roles is timely and wil contribute to the growing knowledge regarding these practitioners and their impact. Methods This qualitative study aimed to improve the understanding of the clinical practice of first‐contact clinicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…Patient responses demonstrated the importance of having adequate time in consultations. Halls et al (2020) found that 71% FCP consultations lasted 20 min; as Langridge (2019) highlighted they are shorter than traditional physiotherapy appointments, thus, rapid‐speed‐of‐thought was required for safe, clinically effective decisions. There are concerns regarding recruitment of sufficiently qualified physiotherapists (NHSE, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Patient responses demonstrated the importance of having adequate time in consultations. Halls et al (2020) found that 71% FCP consultations lasted 20 min; as Langridge (2019) highlighted they are shorter than traditional physiotherapy appointments, thus, rapid‐speed‐of‐thought was required for safe, clinically effective decisions. There are concerns regarding recruitment of sufficiently qualified physiotherapists (NHSE, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…‘Red Flags’ are “clinical features that may be associated with the presence of serious, but relatively uncommon conditions, requiring urgent evaluation” (The Scottish Government, 2015, p. 16). Confidence, vigilance and clinical experience underpin safe practice and reduce the potential for serious pathology being overlooked (Langridge, ). An evaluation (Moffatt, Goodwin, & Hendrick, ) of first contact physiotherapy found that the management of clinical risk is reliant on having clinically experienced MSK physiotherapists with an extended scope of practice in post.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, there was a perception that practice‐based education in a MSK FCP setting would give students an understanding of an advanced area of practice that they were unlikely to encounter elsewhere in their clinical education. Langridge () in a recent study, notes that the emergence of MSK physiotherapists in primary healthcare with the extended scope to independently prescribe and inject and to request medical imaging is moving physiotherapy into a new area of practice. Our participants perceived that by making students aware of this extended scope role through clinical education, it may aspire them to work towards becoming an MSK FCP in the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These themes resonate with the CSP Framework. They are also not dissimilar to those identified by Langridge () who, when exploring competency for First Contact Practitioner roles, suggested: medical assessment and systems knowledge; speed of thought in an uncertain environment; breadth of knowledge; people and communication skills; common sense/simplify; and responsibility and experience were important factors.…”
Section: Discussionmentioning
confidence: 99%